Enhanced discolouration of methyl violet 10B in a gliding arc plasma reactor by the maghemite nanoparticles used as heterogeneous catalyst. Issue 2 (June 2015) - Tiya-Djowe, Antoine; Acayanka, Elie; Lontio-Nkouongfo, G.; Laminsi, Samuel; Gaigneaux, Eric M.
Graphical abstract